The Anaortic Technique with Bilateral Internal Thoracic Artery Grafting - Filling the Gap in Coronary Artery Bypass Surgery - Gomes,Walter J. (2021)
Abstract Coronary artery bypass grafting (CABG) has consolidated its role as the most effective procedure for treating patients with advanced atherosclerotic coronary artery disease, reducing the long-term risk of myocardial infarction and death compared to other therapies and relieving angina. Despite the recognized benefits afforded by surgical myocardial revascularization, a subset of higher-risk patients bears a more elevated risk of perioperative stroke. Stroke remains the drawback of conventional CABG and has been strongly linked to aortic manipulation (cannulation, cross‐clamping, and side-biting clamping for the performance of proximal aortic anastomoses) and the use of cardiopulmonary bypass. Adoption of off-pump CABG (OPCAB) is demonstrated to lower the risk of perioperative stroke, as well as reducing the risk of short-term mortality, renal failure, atrial fibrillation, bleeding, and length of intensive care unit stay. However, increased risk persists owing to the need for the tangential ascending aorta clamping to construct the proximal anastomosis. The concept of anaortic (aorta no-touch) OPCAB (anOPCAB) stems from eliminating ascending aorta manipulation, virtually abolishing the risk of embolism caused by aortic wall debris into the brain circulation. The adoption of anOPCAB has been shown to further decrease the risk of postoperative stroke, especially in higher-risk patients, entailing a step forward and a refinement of outcomes provided by the primeval OPCAB technique. Therefore, anOPCAB has been the recommended technique in patients with cerebrovascular disease and/or calciﬁcation or atheromatous plaque in the ascending aorta and should be preferred in patients with high-risk factors for neurological damage and stroke.